Assessing athletes' mental health literacy - Usenik, J. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction Athletes` mental health has become an increasingly important area of concern. Recent studies have highlighted a comparable or heightened vulnerability to mental health issues among athletes compared to the general population (Kegelaers et al., 2022). Mental health literacy has emerged as a pivotal factor influencing athletes' willingness to seek support during mental health challenges (Bu et al., 2020). This research assesses the reliability and validity of a novel, sports-specific brief tool designed to measure mental health literacy among athletes. Additionally, the study aims to evaluate athletes' mental health literacy alongside other mental health indicators.